(untitled) (Biological Sciences - PJSIR, 2024)
The morbidity of fungal infection is very high all over the world. The treatment of fungal infections is becoming difficult due to expensive antifungal drugs, which have limited efficacy with side effects. Azadirachta indica (neem) tree has been traditionally used for medicinal purposes. Keeping in view the folklore medicinal importance, we determined the antifungal effect of leaves and bark decoctions and infusions in this work. Agar well diffusion method is used for the determination of antifungal potential. Decoctions and infusions prepared from dried and fresh leaves of neem tree showed promising anti- dermatophytic activity against Microsporum canis and Trichophyton tonsurans which was found to be better than antifungal drug fluconazole. This study supports the traditional use of neem trees to treat fungal infections.